Labor disputes resolution, trade unions behavior and legislative and case law in labor during the post-conflict in Colombia (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
This paper develops an overview of the crisis that is facing the collective bargaining model in Colombia, which is increasing the arbitration per year, and hence, the time required for solving the labor disputes. In the second part of the document, there is an analysis of two important facts that influence locally the employment relationships: Trade unions fragmentation and the unions’ membership growth. Then, the third part analyzes the internalization process of the labor disputes in Colombia in the last decade, especially, addressing the evolution of complaints issued in the ILO’s Committee on Freedom of Association (CFA) and the recommendations published by the Committee of Experts on the Application of Conventions and Recommendations (CEACR) of this Entity. Finally, the last part shows the legislative dynamic shown by the Colombian Congress at 2010-2016 periods regarding labor issues, as well as the jurisprudence issued by the Constitutional Court between 1991 and 2016 in Colombia.
Keywords: labor dispute; trade union; union; labor law; case law; bargaining process in Colombia; negotiation; arbitration; Arbitration Court